The origin and evolution of fiqh codification: a preliminary analysis = Asal-usul dan evolusi kodifikasi fiqh: satu analisis - Muhammad, Amanullah; Rahman, Habibur (IIUM Press, 2016)
Throughout the history codification of Islamic law has been given intense attention because of its effect on practical life. Codification plays a positive role to produce appropriate solutions and fair judgments for litigation and disputation. Codification helps establish justice and equality, protect the rights and freedom, and extend security and stability. This paper intends to explore various efforts made to codify Islamic law in the past up to the present through analytical investigation into the related documents, books and literature. The study posits that all the sections of Islamic law, excluding the rituals (ibadat), such as civil, constitutional, judiciary, penal, international, etc. are eligible to be codified. Codification of Islamic law conforms to the legal policy (siyasah shar'iyyah), public wellbeing and the fundamental ruling of permissibility. It is not just valid but rather indispensable as it begets facility for the mankind and removes hardship from them. Thus, codification of Islamic law actualizes the noble objectives of the Shari'ah.